Peptide sequences for protein–protein sliding clampinteractions - Aznabayeva, R.B.; Turgimbayeva, А.М.; Zein, U.O.; Abeldenov, C.K. (Fundamental and Experimental Biology, 2022)
Today antibiotic resistance to pathogenic microorganisms is becoming an increasingly dangerous problem all over the world. At the same time, the need for the development of new antibacterial targets is growing. Since the discovery of sliding clamps in bacteria, a large number of studies have been carried out during which its unique properties, such as the ability to bind to DNA and increase the activity and efficiency of repair and replication proteins, have been discovered, which underlines its important role in maintaining bacteria resistance to DNA damage. At the moment, the numberof partner proteins with which the sliding clamp is able to create functional complexes continues to grow, and therefore the β-clamp is the object of close attention of scientists as a potential solution forfinding new antibiotics. This review article presents some studies highlighting its structure, structure and mechanism of functioning, as well as its ability to form complexes with many partner proteins using a unique PIPβ-clamp binding motif, which is conservative and similar for all partner proteins.